Imaging and Applied Optics 2013
DOI: 10.1364/cosi.2013.cth3b.2
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Light-Field Microscopy

Abstract: By combining a high-resolution image from a standard camera with a low-resolution wavefront measurement from a Shack-Hartmann sensor, we numerically reconstruct a highresolution light field. We experimentally demonstrate the method with a commercially available microscope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Alternatively, a light field could be captured along with a normal, high-resolution widefield image. This would improve resolution at the native object plane and possibly at other planes as well if the two were combined as proposed in [24]. Finally, a lenslet array could be placed at the native image plane of a multi-focal microscope [25] to create many overlapping regions of high resolution and extend the useful axial extent of the 3-D reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a light field could be captured along with a normal, high-resolution widefield image. This would improve resolution at the native object plane and possibly at other planes as well if the two were combined as proposed in [24]. Finally, a lenslet array could be placed at the native image plane of a multi-focal microscope [25] to create many overlapping regions of high resolution and extend the useful axial extent of the 3-D reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…A light field image could also be captured together with a widefield image, the latter providing high-resolution information about the native object plane as proposed in [13]. This method requires splitting the incoming light between two cameras or capturing the light field and widefield images sequentially, which is less suitable for imaging dynamic phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, addressing the large spatial resolution loss implicit in LFM, the group has shown that computational superresolution can be achieved outside the focal plane of the microscope [2,3]. Another super-resolution scheme is combining a Shack-Hartmann wavefront sensor and a standard 2D image to compute a high-resolution microscopic lightfield [14]. LFM has been applied to polarization studies of mineral samples [18] and initial studies for extracting depth maps from the light-field data have been performed in microscopic contexts [8,20].…”
Section: Related Workmentioning
confidence: 99%